A study of selected Filipino web development workers: Their profiles, job satisfaction and predictors of tenure - Cabral, Jennifer L. (Animo Repository, 2001)
This study describes the profiles, identifies the perceived job satisfaction and determines the predictors of tenure of selected Filipino web development workers.Specifically, the study finds out the profile of the Filipino web development workers in terms of their age, education, individual income, civil status, years of work experience and nature of business. Then, the web development workers are asked their perceptions regarding their job satisfaction which include mentally challenging work, equitable rewards, supportive working conditions and having supportive colleagues. Finally, the study determines the predictors for tenure of web development workers in terms of their demographics and job satisfaction.A descriptive research design was used and a relatively new approach to data gathering was utilized through an online questionnaire, which web development workers accomplished using the Internet. With seventy-three web development workers included as part of the sample of the study, results showed that web development workers were mostly single in their twenties and early thirties completed their undergraduate degrees and some even pursued further education through certificate and graduate courses have one to three years work experience and are employed in local information technology companies employing less than fifty people. With regards to job satisfaction, nearly all of the web development workers found their job mentally challenging, had supportive working conditions and supportive colleagues. Only half the selected web development workers found their job equitably rewarding. Finally, using discriminant function analysis, education matched with job satisfaction factor, particularly equitable rewards was the identified demographic variable as a predictor of tenure.